Humans from homosapiens to superhuman Between the momentum of myth and technological development : Ethnographic attempt - Belaidi, Mourad (Journal of Human Sciences, 2025)
Since discovering the first words, man has been obsessed with the supernatural view of what he does not know or thinks he does not know. He has been considered the most elegant strain of the human species, which has survived. Moreover, this dynasty has developed ideas, philosophies and fantasies of its physical and spiritual reality, until this Homosapines came to realize that he is capable of representing traits beyond what he was created for. His obsession hasspread to the sphere of divine traits in various cultures and through many times and ages, until, using, knowledge and science, he reached a great degree of technological development that will allow him to realize the obsession of immorality of living longer and the supernatural powers, and to open up this new asset, a Continuum of technology the same technology that's going to change the human body to take this man to the road of extinction.